1990
DOI: 10.1115/1.2891183
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Micropipette Technique to the Measurement of Cultured Porcine Aortic Endothelial Cell Viscoelastic Properties

Abstract: The viscoelastic deformation of porcine aortic endothelial cells grown under static culture conditions was measured using the micropipette technique. Experiments were conducted both for control cells (mechanically or trypsin detached from the substrate) and for cells in which cytoskeletal elements were disrupted by cytochalasin B or colchicine. The time course of the aspirated length into the pipette was measured after applying a stepwise increase in aspiration pressure. To analyze the data, a standard linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
166
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(180 citation statements)
references
References 0 publications
11
166
3
Order By: Relevance
“…The figure indicates that the rupture force of the bond cluster does not change with viscosity when the viscosity exceeds 50 kPa s. Interestingly, in nature, the value of viscosity for most cells is in the range of tens to thousands of Pa s [8183], implying that cells may adapt their own viscosity by cytoskeleton remodelling to control adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…The figure indicates that the rupture force of the bond cluster does not change with viscosity when the viscosity exceeds 50 kPa s. Interestingly, in nature, the value of viscosity for most cells is in the range of tens to thousands of Pa s [8183], implying that cells may adapt their own viscosity by cytoskeleton remodelling to control adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…The Prony expansion of the time-dependent shear behavior can be formulated as [24] gR(t)=1i=1Ng¯ip(1et/τiG),     where g R ( t )( G R ( t )/ G 0 ) is the dimensionless shear relaxation modulus, G R ( t ) is the shear modulus at the time t , N is the number of terms in the Prony series, g¯ip is the dimensionless Prony series parameter for shear modulus, and τ i G is the relaxation characteristic time. Several studies have included the shear relaxation behavior to express the time-dependent changes in cell stiffness [46, 9]. Similarly, the time-dependent bulk behavior of the material can be expressed in the form of kR(t)=1i=1Nk¯ip(1et/τiK), where k R ( t ) is the dimensionless bulk relaxation modulus, τ i K is the relaxation characteristic time, and  k¯ip is the dimensionless Prony series parameter for bulk modulus.…”
Section: Methodsmentioning
confidence: 99%
“…Micropipette aspiration (MA) technique has been widely used to measure the mechanical properties of different cell types [1, 49]. In this experiment, a cell is aspirated into a micropipette by exerting a negative pressure gradient, and the aspiration length of the cell inside the micropipette is recorded as a function of time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many small-scale biological objects, such as cells, exhibit very little intrinsic optical contrast, requiring preparation such as staining with fluorophores [1] or the deliberate introduction of useful artefacts in the aperture plane which translate phase contrast within the sample into amplitude contrast at the imaging plane [2] . Recent work has suggested that the strongly-varying mechanical properties in these structures may offer further useful contrast in the ultrasound regime [3][4][5][6], however the choice of high resolution and non-destructive mechanical imaging techniques for the study of living biological specimens is remarkably limited. Access to this kind of tool could aid the study of cell processes such as mitosis, migration, force production, mechanosensitivity, and address the myriad dynamic events which underlie the directed stance of living cells towards their environment.…”
Section: Introductionmentioning
confidence: 99%